(untitled) (Indian Journal of Nematology, 2024)
A field experiment on seed treatment of mungbean with Trichoderma harzianum (Th) and Pseudomonas fluorescens (Ps) @1 and 2% w/w alone and in combination with carbofuran @ 1 and 2 kg a.i./ha showed minimum population of reniform nematode, Rotylenchulus reniformis in the combined application of Th and carbofuran at harvest. Grain yield was highest in the individual application of Th (1%) and carbofuran (1kg a.i./ha). Similarly grain yield was better in individual application than the combined application of carbofuran with Ps. On the reniform nematode population combined application of Ps with carbofuran reduction was significant except Ps 2% with carbofuran 2 kg a.i./ha while yield was highest with Ps (2%) in individual application. Thus, Th and Ps 1% each with carbofuran (1 kg a.i./ha) reduced reniform nematode multiplication significantly.